Isolation and Diagnosis of Escherichia coli bacteria from Patients with Urinary Tract Infections and Bacteriosis and Studying their Sensitivity to Some Antibiotics and Nanobodies - Hamad, Rania Maged; Al-Juboory, Yassien Hussain Owaied; Abdullah, Iman Tajer (Journal for Research in Applied Sciences and Biotechnology, 2023)
The current study included the collection of 120 clinical samples (diuresis, blood) from patients visiting Baghdad city hospitals (Yarmouk Teaching Hospital, Central Children's Teaching Hospital, and Baghdad Teaching Hospital) for the period from November 2022 to February 2023. 30 discharge samples were collected from healthy people as a control group. The samples were within different ages and genders ranging from 14 years to 52 years. 10% of the E bacteria have been isolated coli of blood and 150% of blood based on phenotypic and culture characteristics and biochemical tests and the diagnosis was confirmed using the phytic device. The results of the sensitivity test of bacterial isolates using the tablet method of diffusion showed that most of the isolates were resistant to the antibiotics used, where the percentage of resistance to Tetracycline (96%), (84%) Nitrofurantoin, (82%) Ceftriaxone, (66%) Meropenem, (52%) Ciprofloaxcine, (70%) Gentamicin, (80%) Amikacin, (46%) Imipenem, Nalidixic acid (40%). The antimicrobial activity of gold and titanium nanoparticles was evaluated against 15 bacterial isolates (5 isolated from diuretic samples, 5 exit samples, 5 blood samples) using the diffusion method by gratigran. The results showed that the nanoparticles had a clear inhibitory effect against the studied isolates where the average inhibition diameters ranged between 17-22 mm and the MIC value (Minimal inhibitory concentration) was between 64-126.